Humanization of Islamic Education Within the Framework of Constructivism (Literature Analysis on the Dialectic of Paulo Freire and Al-Ghazali's Thought) - Alfabanni, Tunde Ahmed; Abinnashih, Ibnu (PT. Pusmedia Group Indonesia, 2025)
Islamic education today faces dehumanization challenges where learning overemphasizes cognitive aspects while neglecting spiritual and moral dimensions. This phenomenon necessitates a more humanistic and constructive approach relevant to 21st-century educational demands. This study aims to analyze and discover a synthesis between humanistic and constructivist values in developing an Islamic education model through a qualitative approach using library research. Data were collected from various literature sources, international journal articles, and academic works relevant to the topic, then analyzed using thematic content analysis with NVivo 12 software. The findings indicate that humanistic values emphasize the importance of humanizing education through freedom, respect, and recognition of learners’ potential, while constructivism highlights the active role of learners in constructing knowledge through experience, interaction, and reflection. The synthesis of both approaches results in a transformative Islamic education paradigm framework consisting of five integrated dimensions: spiritual-ethical foundation, critical dialogical pedagogy, experiential constructivist learning, character-based assessment, and socially engaged praxis. This framework operationalizes the integration of Al-Ghazali's tazkiyat al-nafs (soul purification) with Freire's conscientization through a cyclical learning model. The synthesis of both approaches results in an Islamic education paradigm that is student-centered, integrating spirituality, rationality, and critical awareness, and is highly relevant to the demands of 21st-century education. This study is limited to library research without empirical field testing; therefore, further research is recommended to validate this framework through action research in Islamic educational institutions and develop culturally contextualized assessment instruments. Theoretically, this study enriches the discourse of Islamic educational philosophy by bridging modern thought and classical Islamic traditions. Practically, it contributes to the development of curricula and teaching strategies that are humanistic, constructive, and capable of addressing the challenges of globalization and educational dehumanization.